Efficacy, Safety, and Subject Satisfaction After AbobotulinumtoxinA Treatment of Upper Facial Lines. Issue 12 (December 2018) - Hexsel, Doris; Cartier, Hugues; Hedén, Per; Delmar, Henry; Bergentz, Per; Camozzato, Fernanda; Siega, Carolina; Skoglund, Cecilia; Edwartz, Carolina; Rees, Diane; Kestemont, Philippe
Abstract : BACKGROUND: Botulinum toxins are the treatment of choice for wrinkles in the upper third of the face. OBJECTIVE: The purpose of this study was to evaluate the efficacy, safety, and subject satisfaction of abobotulinumtoxinA (ABO) for treatment of upper facial lines. MATERIALS AND METHODS: Subjects aged 35 to 50 years with moderate-to-severe upper facial lines were included in this study. Subjects received a maximum of 125 s.U. ABO in at least 2 indications with optional touch-up after 2 weeks. Assessments included wrinkle severity, global aesthetic improvement, subject satisfaction, and adverse events (AEs) 1, 3, and 6 months after treatment. RESULTS: At Month 1, 100, 94, and 93% of subjects were responders in dynamic glabellar, lateral canthal, and forehead lines, respectively. All subjects were improved 1 month after treatment, and the majority of the subjects were still improved after 6 months. After treatment, most subjects were satisfied with the appearance of their face, felt better about themselves, and agreed that the treatment made them look the way they feel. Seven subjects (22%) had 8 ABO-related AEs (mild–moderate); headache was most commonly reported (9%). CONCLUSION: AbobotulinumtoxinA effectively treated upper facial lines, with high patient satisfaction. Treatment was generally well-tolerated.